Do Social and Institutional Factors Improve the Quality of Environment? Evidence from 5 ASEAN Economies - Agussani Agussani (Jurnal Studi Pemerintahan, 2021)
This study aims to analyze the impact of social (human development, educational development, and financial development) and institutional factors (corruption and administrative effectiveness) on environmental quality. For this purpose, the study utilized the data of 5 ASEAN economies over the period of 2000-2018. Study used Brush Pagon LM and Pearson CD for testing the cross-section dependency of among variables. Results of OLS depicts positive effects of human development, educational development, and financial development and administrative effectiveness on environmental quality while corruption have negative effects on environmental quality. Results suggests that government should promote social and institutional factor for improving the environmental performance.